Balleans of bounded geometry and G-spaces - Protasov, I.V. (Algebra and Discrete Mathematics, 2008)
A ballean (or a coarse structure) is a set endowed with some family of subsets which are called the balls. The properties of the family of balls are postulated in such a way that a ballean can be considered as an asymptotical counterpart of a uniform topological space.